Pemenuhan Hak Pemilih dalam Pemilu (Studi Tata Kelola Formulir C6 di Kabupaten Banjarnegara dan Kabupaten Magelang dalam Pemilu Serentak 2019) - Wibisono, Wahyudi; Fitriyah, Fitriyah; Hidayat, Nur (Universitas Batanghari Jambi, 2024)
The aim of this research is to 1) analyze the work of the Magelang Regency KPU and Banjarnegara Regency KPU in fulfilling voters' political rights in the 2019 Election; 2) analyze the influence of Form-C6 management on voters in the 2019 Election in Magelang Regency and Banjarnegara Regency; and 3) analyze the KPU's strategy to optimize administrative management of form C-6. The method used in this research is a qualitative method with informants namely KUPD, City/Regency Banwaslu, District KPPS, TPS supervisors, and voters both in Banjarnegara Regency and those in Magelang Regency. The results of the research show that there are voters who are registered on the Permanent Voter List (DTP) but did not receive the C6 Form in the 2019 Election, in Magelang Regency data collection and management is complete while Banjarnegara Regency is the district with the most C6 form returns and the KPU's strategy is to optimize administrative management of form C-6 is carried out by opening complaints and services to people who have registered in the DPT.